Rancang Bangun Sistem E-Katalog Toko Bangunan Berbasis Web pada Platform KatalogQu di PT Era Cipta Digital - Fauzy, Muhammad; Muhathir (Jurnal Ilmu Komputer dan Teknologi Informasi, 2026)
The advancement of technology has driven the use of social media to promote products, including in the building materials industry. To address this, the author designed a website e-catalog as a solution for promoting building materials products. This website serves as a sub-website of the KatalogQU platform at PT. Era Cipta Digital, featuring a ready-to-sell template that can be customized through an admin dashboard. Store owners can adjust the website's appearance according to their needs. The site displays building materials products with various features and appealing layouts. The E-Catalog system is built using the Laravel framework, with key features such as CRUD for products and categories, appearance settings, and catalog content management. The outcome is a sub-website that can be used by various building material stores, making it easier for store owners to promote and sell their products online. This website allows building material stores to increase product visibility and expedite transactions, providing store owners with a more efficient way to run their business.